Potent inhibition of respiratory syncytial virus replication using a 2-5A-antisense chimera targeted to signals within the virus genomic RNA - Player, Mark R. (National Academy of Sciences, 1998)
The 2-5A system is a recognized mechanistic component of the antiviral action of interferon. Interferon-induced 2-5A synthetase generates 2-5A, which, in turn, activates the latent constitutive RNase L that degrades viral RNA. Chemical conjugation of 2-5A to an antisense oligonucleotide can target the 2-5A-dependent RNase L to the antisense-specified RNA and effect its selective destruction. Such a 2-5A-antisense chimera (NIH351) has been developed that targets a consensus sequence within the respiratory syncytial virus (RSV) genomic RNA. NIH351 was 50- to 90-fold more potent against RSV strain A2 than was ribavirin, the presently approved drug for clinical management of RSV infection. It was similarly active against a variety of RSV strains of both A and B subgroups and possessed a cell culture selectivity index comparable to ribavirin. In addition, the anti-RSV activity of NIH351 was shown to be virus-specific and a result of a true antisense effect, because a scrambled nucleotide sequence in the antisense domain of NIH351 caused a significant decrease in antiviral activity. The 2-5A system’s RNase L was implicated in the mechanism of action of NIH351 because a congener with a disabled 2-5A moiety was of greatly reduced anti-RSV effectiveness. These findings represent an innovative approach to the control of RSV replication.